Analisis Nilai Pada Tradisi Popene’e Dalam Pernikahan Suku Lauje Desa Ambesia Induk Kecematan Tomini Kabupaten Parigi Moutong - A, Sulis; I, Idrus; S, Fira; R, Niluh; A, Alif (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study discusses the Analysis of Values in the Popene'e Tradition in Lauje Tribe Weddings held in Ambesia Induk Village, Tomini District, Parigi Moutong Regency. The Popene'e tradition is a form of cultural heritage that is still carried out from generation to generation by the Lauje tribe, especially in a series of wedding processions. The purpose of this study  is to identify and describe the eight stages of the implementation of the Popene'e tradition and to reveal the cultural, social, and religious values contained therein. This  study uses a qualitative approach with a descriptive method. Data collection techniques are carried out through direct observation, in depth interviews with traditional leaders, the Ambesia community, and the community participating in the tradition, as well as documentation of the implementation of the  Popene'e tradition. Data analysis uses the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions.  The results of the study indicate that theiPopene'e tradition consists of eight main stages, each of which has its own symbols and philosophical meanings, such as responsibility in the household, loyalty, hard work, mutual cooperation, and respect for ancestors. The  values contained in this tradition include: social values in the form of mutual cooperation and solidarity between residents, cultural values in  the form  of  preserving customs, religious values reflected in the form of prayer and spiritual respect and educational values of character building.